A Novel Data Hiding Scheme Based on Fused Adaptive and Nonadaptive Technique (International Journal of Engineering and Computer Science, 2015)
Steganography is a technique of hiding the secret information. Steganography hides the existence of the secret data and make the communication undetectable. Secret data can be communicated in an appropriate multimedia carrier such as image, audio or video. Image steganography is extensively used technique. In this technique secret data is embedded within the image. Steganography techniques can be categorized into two groups - adaptive and non-adaptive. Each of these have its strengths and weaknesses. Adaptive steganography embeds the secret information in the image by adapting some of the local features of the image. Non-adaptive steganography embeds secret data equally in each and every pixel of the image. Several techniques have been proposed for hiding the secret data. Least significant bit replacement is the most common method. This is because it is simple and easy to implement. Discrete wavelet transform is also a widely used technique for embedding secret information. This paper propose a novel steganographic approach for hiding the secret data by fusing both adaptive and non-adaptive methods of steganography. This will give a more secure approach for hiding the secret information as the secret embedded image is almost same and totally indistinguishable from the original image by the human eye. Also the retrieved secret image is same as the original secret image. This is proved by means of high values for PSNR and very little values for MSE.